A RELAÇÃO DIALÉTICA ENTRE EDUCAÇÃO E POLÍTICA: UMA ANÁLISE DA ATUAÇÃO POLÍTICA DOS JOVENS ESTUDANTES SECUNDARISTAS - Rocha Junior, João Mendes da (2018)
This text is the result of the research carried out for the preparation of the Master's thesis in education. The research problem falls within the scope of educational policy and assumes that school education is a constitutive element of human formation. Among its contributions is the political formation of students, which has been the subject of a number of criticisms, mainly by sectors of society announcing that the school should be "neutral" and therefore not addressing such issues. In this way, this research aims to contribute to the debate on education and politics. Therefore, this work sought to problematize the political action of the students and the reasons why it is affirmed that the school cannot be a space for political practice. It is adopted as method of research the historical and dialectical materialism and the use of its categories as totality, contradiction and mediation. Empirical data collected at the Colégio Estadual Francisco Carneiro Martins in Guarapuava-PR is used as source, which provide information about the movement of student occupation occurred in 2016 in this school campus. In our understanding, school occupations are the materialization of the contradictions between education and politics, and this act is endowed with an inherent contradiction of the class struggle, since the mediations acting for these processes are endowed with a political, ideological and formation view of the human being related to the material production of social life. In this way, education and politics as separate entities shows itself as impossible. School education is political in its essence, because it is the place of introjection of norms, knowledge and ideologies that express social contradictions, the production and reproduction of life and, therefore, also space of struggles. This space became a source of concern for the ruling class when it saw the insurrection of several student demonstrations contrary to the directions of proposed formal education. Thus, we see that the defense of an "apolitical" school education is of interest to a policy that seeks to domesticate people, which, more than succeed in creating a specific law on this subject, seeks to inhibit any focus of resistance that may arise in a space like the school.